Small intestine melanosis caused by clofazimine - Wei-qiang Wang; Peng Li; Guang-ming Tang; Zhao Li; Zhong-min Chen (Medicine, 2026)
Rationale: Melanosis coli is a rare condition characterized by abnormal pigmentation of the gastrointestinal mucosa, most commonly involving the colon. Involvement of the small intestine is exceedingly rare, with only a few cases documented in the literature. Here, we present a case of small-intestinal melanosis and explore its potential pathogenesis and clinical significance. Patient concerns: A 40-year-old male presented with a 6-month history of abdominal pain and altered bowel habits. He had been taking clofazimine (100 mg/d) for pulmonary tuberculosis for 7 months. Notably, his symptoms and skin hyperpigmentation began 1 month after initiating clofazimine therapy. Total enteroscopy revealed diffuse gray pigmentation of the duodenal, jejunal, and ileal mucosa. Histological analysis showed lipofuscin-like granules resembling those observed in colonic melanosis. Methylene blue staining demonstrated uniform uptake, with brownish granules at the villous tips, producing a coral-like appearance. Histopathological examination confirmed the presence of chronic inflammation with mucosal pigment deposition. Diagnoses: Small-intestinal melanosis secondary to clofazimine therapy. Interventions: Clofazimine was discontinued, and no further treatment was administered. Outcomes: Three months after stopping clofazimine, the patient’s symptoms resolved, skin pigmentation faded, and follow-up enteroscopy showed normal mucosal color throughout the small intestine. Lessons: Intestinal melanosis is a rare disease that, in this case, may be related to long-term clofazimine use. Clinicians should consider this diagnosis in patients with unexplained intestinal pigmentation, particularly in those taking clofazimine. Further research is needed to elucidate its natural history and underlying mechanisms.